Tolerance to Excess-Boron Conditions Acquired by Stabilization of a BOR1 Variant with Weak Polarity in Arabidopsis - Wakuta, Shinji; Fujikawa, Teppei; Naito, Satoshi; Takano, Junpei (Frontiers in Cell and Developmental Biology, 2016)
Boron (B) is a metalloid that is essential for plant growth but is toxic when present in excess. Arabidopsis BOR1 is a borate exporter, facilitating B translocation from root to shoot under limited-B conditions. BOR1 shows stele side polar localization in the plasma membrane of various root cells, presumably to support B translocation toward the stele. BOR1 is degraded under high-B supply through vacuolar sorting via ubiquitination at the K590 residue to prevent the accumulation of B to a toxic level in shoots. A previous study showed that overexpression of BOR1 under control of the cauliflower mosaic virus 35S RNA promoter improved the growth of Arabidopsis under limited-B conditions without affecting the growth under sufficient-to-excess-B conditions. In this study, we unexpectedly found that ubiquitous expression of a stabilized BOR1 variant improved tolerance to excess-B in Arabidopsis. We established transgenic plants expressing BOR1-GFP fused with hygromycin phosphotransferase (HPT) and BOR1(K590A)-GFP-HPT under control of the ubiquitin 10 promoter. BOR1-GFP-HPT and BOR1(K590A)-GFP-HPT were expressed in various cell types in leaves and roots and showed weak polar localization in root tip cells. BOR1-GFP-HPT, but not BOR1(K590A)-GFP-HPT, was degraded through an endocytic pathway under high-B conditions. Transgenic plants with the stabilized variant BOR1(K590A)-GFP-HPT showed improved root and shoot growth under excess-B conditions. The concentration of B was greater in the shoots of plants with BOR1(K590A)-GFP-HPT or BOR1-GFP-HPT than in those of untransformed wild-type plants. These results suggest that BOR1(K590A)-GFP-HPT confers tolerance to excess-B by excluding B from the cytosol of shoot cells. Results from this study indicate the potential for engineering the trafficking properties of a transporter to produce plants that are tolerant to mineral stress.